2020
DOI: 10.1155/2020/4370983
|View full text |Cite
|
Sign up to set email alerts
|

miR-10a in Peripheral Blood Mononuclear Cells Is a Biomarker for Sepsis and Has Anti-Inflammatory Function

Abstract: Background. Recent literature has reported the use of circulating microRNAs (miRNAs) as biomarkers for sepsis. Immune cells play an essential role in the pathophysiology of sepsis. The aim of this prospective study was to identify miRNAs in peripheral blood mononuclear cells (PBMC) that could differentiate between sepsis and infection based on Sepsis-3 definition. Methods. A total of 62 patients (41 with sepsis and 21 with infection suffering from pneumonia but without sepsis) and 20 healthy controls were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This is an explanation for our observation, that the number of low-density granulocytes co-purifying with the PBMC fraction varies highly between patients. Although some of the studies depicting the problem of contaminating, co-purifying low-density granulocytes have been published a decade ago, it is still common practice today to use density gradient centrifugation for PBMC isolation from patients with sepsis (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). This goes along with a lack of reported information on the isolation purity and identification of the contained cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This is an explanation for our observation, that the number of low-density granulocytes co-purifying with the PBMC fraction varies highly between patients. Although some of the studies depicting the problem of contaminating, co-purifying low-density granulocytes have been published a decade ago, it is still common practice today to use density gradient centrifugation for PBMC isolation from patients with sepsis (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). This goes along with a lack of reported information on the isolation purity and identification of the contained cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to measure DUSP22 methylation in a cohort of neonatal septic patients in order to evaluate its potential as prognostic biomarkers in neonatal sepsis. Regarding MIR10A , it has been shown that miR-10a levels in PBMC at admission were significantly lower in sepsis patients compared with non-septic patients with infection, and with healthy controls ( 58 ). Moreover, miR-10a levels were found to predict 28-day mortality and negatively correlate with disease severity as well as levels for C-reactive protein, procalcitonin, and inflammatory cytokines such as IL-6, TNF-α, and MCP-1 ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MIR10A , it has been shown that miR-10a levels in PBMC at admission were significantly lower in sepsis patients compared with non-septic patients with infection, and with healthy controls ( 58 ). Moreover, miR-10a levels were found to predict 28-day mortality and negatively correlate with disease severity as well as levels for C-reactive protein, procalcitonin, and inflammatory cytokines such as IL-6, TNF-α, and MCP-1 ( 58 ). Regarding MIR886 , it has been shown that miR-886-5p is increased in human monocyte-derived macrophages as a response to mycobacterial infection at 48 h ( 59 ), and the isoform hsa-miR-886-3p was present at higher levels in PBMCs from critically ill patients infected with H1N1 influenza virus than PBMCs from healthy controls ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory and immunosuppressive function of RACev may thus be associated with Treg-derived EV secretion, as Tregs modify the host antigen-presenting cell function via miR-142-3p (2285-fold upregulated in RACev), and EVs may escape T cell recognition as shown previously ( Supplementary Figure 3E ) ( 39 ). The miRs have broad functions in immune regulation, for example, miR-10a, miR-21, miR-24 are expressed in immune cells and function as “fine-tuners” for innate and adaptive immune responses ( 40 , 41 ). In adaptive immunity, they are implicated in the biological processes including pathways involved in the T and B cells central and peripheral tolerance, as well as their function ( 40 ).…”
Section: Discussionmentioning
confidence: 99%